Linguo-Pedagogical Design of Open Question Items in the Context of Digitalization - A. V. Alikina; D. V. Maltsev (Высшее образование в России)
Interdisciplinary approach to the development and creation of open question items for assessment procedures in accordance with the digital transformation strategy and the new requirements for state accreditation of educational programs of higher education has been presented in the article. It has been revealed the content of the author’s terms including linguo-pedagogical mastery, linguo-pedagogical design, linguistic correctness and methodological literacy of test tasks. On the basis of scientometric analysis carried out due to the scientific electronic library elibrary it has been determined the chronological activity and subject correlation of publications of native researchers on testing students. Based on the results of a survey of teachers from 11 regional universities the main difficulties in the preparation of testing and assessment materials are summarized. Examples of test items in disciplines taught at a multidisciplinary polytechnic university are analyzed. Typical errors in the wording of questions, reference answers and evaluation criteria have been identified by the methods of erratological analysis and the reasons for their appearance have been summarized. To model the linguo-pedagogical design of test tasks the concept of an epistemic situation is used, its four components are described: ontological (subject-content definition of objects and elements of control), methodological (selection of types and types of tasks depending on the level of measured outcomes of learning), communicative-pragmatic (ensuring the comprehensibility of the text of the test task) and technological (technical implementation of the automated check of free response). Methods of test tasks modification with the help of modern digital services are proposed. As a result of the study, the authors formulate recommendations for the implementation of the linguo-pedagogical design of open question items with a focus on their implementation in the digital environment.